2017
DOI: 10.1136/jclinpath-2017-204403
|View full text |Cite
|
Sign up to set email alerts
|

Serine proteases of the complement lectin pathway and their genetic variations in ischaemic stroke

Abstract: AimsThe aim of the current study was to assess the proteolytic activities of collectin-bound MASP-1 and MASP-2 in the blood of patients with ischaemic stroke, as well as the association of their six genetic polymorphisms (rs3203210, rs28945070, rs28945073 in MASP1 gene and rs2273343, rs12711521, rs147270785 in MASP2 gene) with this pathology.MethodsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…We did not find differences between IS patients and controls, but ICH patients had significantly lower PLG protein amounts. MASP1 concentration was increased in myocardial infarction, however, in IS was reported to be either increased or decreased, whereas in ICH and SAH, lower levels were found (56)(57)(58). In our study, we detected higher MASP1 protein amount in IS than in healthy controls as well as in ICH.…”
Section: Review Of the Literature And Integrative Evaluationcontrasting
confidence: 40%
“…We did not find differences between IS patients and controls, but ICH patients had significantly lower PLG protein amounts. MASP1 concentration was increased in myocardial infarction, however, in IS was reported to be either increased or decreased, whereas in ICH and SAH, lower levels were found (56)(57)(58). In our study, we detected higher MASP1 protein amount in IS than in healthy controls as well as in ICH.…”
Section: Review Of the Literature And Integrative Evaluationcontrasting
confidence: 40%
“…Double Masp1/Masp2 knock-out ischemic mice were also not protected (Orsini et al, 2016). In a study carried out in the Armenian population, it was found that patients with ischemic stroke had higher proteolytic activity of MASP-1 and MASP-2, than controls (5.8 and 3.7 times more, respectively) (Tsakanova et al, 2018). Taken together, the evidence warrants further investigation with MASP levels and polymorphisms (Tables 1 and 2) in the susceptibility to cerebral vascular ischemia, especially within the context of COVID-19 disease.…”
Section: Cerebrovascular Diseasesmentioning
confidence: 96%
“…Particularly, the results indicated that the activities of MASP-1 and MASP-2 are elevated in the blood of ischemic stroke patients compared with control subjects. 11 , 14 Moreover, we found that the rs3203210 and rs28945073 single nucleotide polymorphisms (SNPs) in the MASP1 gene and the rs147270785 SNP in MASP2 are strongly associated with ischemic stroke. 14 …”
Section: Introductionmentioning
confidence: 98%
“…11 , 14 Moreover, we found that the rs3203210 and rs28945073 single nucleotide polymorphisms (SNPs) in the MASP1 gene and the rs147270785 SNP in MASP2 are strongly associated with ischemic stroke. 14 …”
Section: Introductionmentioning
confidence: 98%